2012
DOI: 10.4028/www.scientific.net/amr.430-432.1155
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Visual Analyses on Failure Criteria of Slope Stability in Strength Reduction Finite Element Method

Abstract: The failure criteria in strength reduction FEM are not unified and often affected greatly by researcher’s experience and judgment, so it is necessary to discuss the applicability and the difference of some various criteria of instability of slope. According to the thought of visualization in real time computing, the corresponding visual program is developed based on some common failure criteria adopted simultaneity in the strength reduction FEM. Then, through the real-time visual interface, the comparisons of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…The parameters of cohesion (c) and the internal friction angle (ϕ) maintain consistent weakening and contribution ratios throughout the progressive degradation of the geotechnical body; in this way, the aforementioned process may appear straightforward. However, it fails to align with actual slope failure phenomena [22][23][24][25][26]. Practical experiments have shown that the cohesion (c) and the internal friction angle (ϕ) do not reach their peak strength and critical limit at the same time, and different reduction coefficients should be used for the double-parameter reduction with respect to the double-strength parameter characteristics and weakening mechanisms [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…The parameters of cohesion (c) and the internal friction angle (ϕ) maintain consistent weakening and contribution ratios throughout the progressive degradation of the geotechnical body; in this way, the aforementioned process may appear straightforward. However, it fails to align with actual slope failure phenomena [22][23][24][25][26]. Practical experiments have shown that the cohesion (c) and the internal friction angle (ϕ) do not reach their peak strength and critical limit at the same time, and different reduction coefficients should be used for the double-parameter reduction with respect to the double-strength parameter characteristics and weakening mechanisms [27,28].…”
Section: Introductionmentioning
confidence: 99%